2020
DOI: 10.1074/jbc.ra119.011570
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of human type-3 inositol triphosphate receptor reveals the presence of a self-binding peptide that acts as an antagonist

Abstract: Calcium-mediated signaling through inositol 1,4,5-triphosphate receptors (IP3Rs) is essential for the regulation of numerous physiological processes, including fertilization, muscle contraction, apoptosis, secretion, and synaptic plasticity. Deregulation of IP3Rs leads to pathological calcium signaling and is implicated in many common diseases, including cancer and neurodegenerative, autoimmune, and metabolic diseases. Revealing the mechanism of activation and inhibition of this ion channel will be critical to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 53 publications
1
40
0
Order By: Relevance
“…This domain-swapped arrangement is likely made possible by the relatively long lateral TM4-5 helix. Notably, the cryo-EM density maps of IP 3 R1 solved in this study are of higher quality than any of the IP 3 R structures reported to date [4][5][6][7] . The improved density features were observed throughout the entire channel protein, and most of the protein domains exhibit wellresolved side-chain densities (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…This domain-swapped arrangement is likely made possible by the relatively long lateral TM4-5 helix. Notably, the cryo-EM density maps of IP 3 R1 solved in this study are of higher quality than any of the IP 3 R structures reported to date [4][5][6][7] . The improved density features were observed throughout the entire channel protein, and most of the protein domains exhibit wellresolved side-chain densities (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 62%
“…The improved density features were observed throughout the entire channel protein, and most of the protein domains exhibit wellresolved side-chain densities (Supplementary Figs. 3 and 4) to allow for unambiguous building of atomic models for~83% of the protein, including additional structural elements in the TM region that were not previously resolved (see "Methods" section; Supplementary Table 1) [4][5][6][7] . Both IP 3 R1-ND and IP 3 R1-LMNG structures showed the additional protein densities at the lumenal vestibule that were discerned as two antiparallel, membraneassociated (MA) helices, MA1 and MA2, that form a membraneembedded helix-loop-helix structure comprising residues P2307-G2349 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A). We assessed the affected residues using published IP 3 R structures 24‐26 . p.Val615 is located in the armadillo repeat domain (ARM1), just after the IP 3 ‐binding domain (running from aa 1 to ~ aa 600).…”
Section: Resultsmentioning
confidence: 99%
“…We assessed the affected residues using published IP 3 R structures. [24][25][26] p.Val615 is located in the armadillo repeat domain (ARM1), just after the IP 3 -binding domain (running from aa 1 to~aa 600). p.Arg2524 is located in the transmembrane domain (TMD) and lies in the channel pore (Fig.…”
Section: Genetic Findingsmentioning
confidence: 99%